ANALISIS DAMPAK LALU LINTAS AKIBAT DISRUPSI PADA SAAT ACARA BESAR DENGAN MENGGUNAKAN MODEL SIMULASI MIKRO - Zukhruf, Febri; Maulana, Andrean; Nugroho, Taufiq Suryo; Purwanti, Oka; Santoso, Satya Ananda; Khaerul Ikhsan, Robby Septiandi (Jurnal Jalan Jembatan, 2024)
This paper discusses traffic performance under major and disruption events on the road network. Traffic on the road network is modelled based on a microsimulation model by considering conditions without disruption, with disruption, and with disruption accompanied by the mitigation schemes. The simulation model used in this paper models the driving behaviour at the micro level that can be used to simulate interactions between vehicles and traffic performance in response to changes in road capacity due to disruption. The model is tested on a road network with significant sports events and potential natural disasters. Traffic flow is estimated based on information from previous events. The results of the microsimulation modelling show that the disruption scenario can reduce road network performance by up to 43%, with total delays that can increase up to five times. In addition, the mitigation schemes to reduce the disruption contribute to maintaining good traffic performance. This paper's framework can potentially be used to assess the impact of traffic disruptions during significant events. Furthermore, it can evaluate alternative strategies to overcome the disruption.